Comonotone approximation pointwise estimates for twice differentiable functions - Dzjubenko, H. A.; Lystopad, Vladimir; Shevchuk, L. A. (My University, 1994)
An estimate for polynomial approximation of a twice differentiable comonotone (i.e. piecewise-monotone) function is obtained in terms of k-th modulus of continuity of the function in question.
Keywords: approximation by polynomials; наближення многочленами; полиномиальная аппроксимация; кафедра вищої математики імені проф. Можара В. І.